2013
DOI: 10.1093/eurheartj/eht290
|View full text |Cite
|
Sign up to set email alerts
|

An individual patient meta-analysis of five randomized trials assessing the effects of cardiac resynchronization therapy on morbidity and mortality in patients with symptomatic heart failure

Abstract: AimsCardiac resynchronization therapy (CRT) with or without a defibrillator reduces morbidity and mortality in selected patients with heart failure (HF) but response can be variable. We sought to identify pre-implantation variables that predict the response to CRT in a meta-analysis using individual patient-data.Methods and resultsAn individual patient meta-analysis of five randomized trials, funded by Medtronic, comparing CRT either with no active device or with a defibrillator was conducted, including the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
344
5
31

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(390 citation statements)
references
References 48 publications
(57 reference statements)
10
344
5
31
Order By: Relevance
“…A total of 1100 patients experiencing a primary endpoint will generate 90% statistical power to demonstrate a significant reduction in the incidence of the primary endpoint, accounting for three equally spaced interim analyses (α = 0.05) and assuming a true intent‐to‐treat hazard ratio (HR) of 0.82 for ‘AdaptivCRT’ compared with ‘Conventional CRT’. With randomization of 3000 patients enrolled over 3 years and followed for 2.5 years, 1100 events are expected when the true control arm event‐free rate is 75% at 2 years (which is consistent with results from MADIT‐CRT,26 REVERSE,27 RAFT,28 Cleland's CRT meta‐analysis,29 and the adaptive CRT study18, 19). …”
Section: Methodssupporting
confidence: 68%
“…A total of 1100 patients experiencing a primary endpoint will generate 90% statistical power to demonstrate a significant reduction in the incidence of the primary endpoint, accounting for three equally spaced interim analyses (α = 0.05) and assuming a true intent‐to‐treat hazard ratio (HR) of 0.82 for ‘AdaptivCRT’ compared with ‘Conventional CRT’. With randomization of 3000 patients enrolled over 3 years and followed for 2.5 years, 1100 events are expected when the true control arm event‐free rate is 75% at 2 years (which is consistent with results from MADIT‐CRT,26 REVERSE,27 RAFT,28 Cleland's CRT meta‐analysis,29 and the adaptive CRT study18, 19). …”
Section: Methodssupporting
confidence: 68%
“…In contrast, patients with non‐LBBB morphology allocated to the CRT arm showed a clinical benefit only when the QRS duration was 160 ms or longer (HR 0.52, 95% CI 0.29–0.96; P  = 0.033) 5. In addition, an individual patient meta‐analysis on data from 3872 patients randomized in five clinical trials showed that patients with LBBB morphology exhibited larger benefit from CRT than patients with non‐LBBB morphology, although the difference was not statistically significant 23. Importantly, QRS duration was significantly associated with reductions in all‐cause mortality and the rates of the composite endpoint, particularly when QRS duration exceeded 140 ms 23.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned separate analyses showing that QRS duration and morphology are important determinants of clinical benefits of CRT have led to the investigation of the interaction between QRS duration and morphology and its effects on CRT outcomes 5, 10, 23, 24. The sub‐analysis of the RAFT trial (after excluding patients with ventricular pacing and permanent atrial fibrillation) showed that regardless the QRS duration, patients with LBBB morphology who were randomized to CRT with defibrillator function showed a reduction in the rates of the primary outcome (composite endpoint of all‐cause mortality and heart failure hospitalization) (HR 0.640; 95% CI 0.524–0.781; P  < 0.001) 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22---24 However, in a recent meta-analysis including five randomized trials, QRS duration was a powerful predictor of CRT effectiveness. 25 Moreover, a sub-analysis of the MADIT-CRT trial associated longer QRS (>150 ms) with benefits of CRT in LV function, morbidity and mortality. 7 The REVERSE study confirmed the importance of QRS duration and LBBB pattern in CRT outcomes.…”
Section: Discussionmentioning
confidence: 99%